0171 A Simulated Burns Course Using Moulage: Can We Use It To Help Trainees And Other Healthcare Professionals Improve Their Confidence By Increasing The Realism Of Simulation?. (1st November 2014) - Medjoub, karima; Stewart, Ian; Edgar, Simon; Widdowson, Dan; Stewart, Ken
Abstract : Background: Dealing with major burns can be a stressful situation during the acute phase of management. Due to the lack of training around the care of burns, they can be often managed inadequately, which can lead to devastating and long-term complications. Healthcare professionals in our board are eager to learn about the best way to care for these patients. Cue from burn patients are often visual as well as the general observations. Currently the EMSB (Emergency Management of Severe Burns) course offers a one day teaching lectures and scenarios to different healthcare professionals. What we offer is the use of Hi-fidelity mannequin, complemented with Moulage, and the use of reflective debriefing. Can we use simulation to make them more confident and improve their practical knowledge around care of burns using Moulage? Methodology: The scenarios objectives were mapped to plastic surgery curriculum. A hi-fidelity simulation centre will be used to launch the pilot course intended in the first instance to the regional burns unit/ plastic surgery department. Feedback will be collated to establish the positive outcomes and any possible deficiencies to tailor future courses. A debrief session facilitated by a tutor experienced in reflective debrief will fellow each scenario. Results: We hope to produce a model to train doctors, nurse and allied health care professionals in the care of severe burns in a safe environment. Future plans are to establish in-situ simulation in the emergency department to further increase the realisms and relevance to the individuals taking part in the course. Potential impact: Improving practical knowledge and confidence amongst healthcare professionals is our short-term goal, ultimately hoping to impact on patient outcome, which we understand will require a long journey of translational research. Reference: The Education Committee of the Australian and New Zealand Burn Association, 2012. Emergency Management of Severe burns (EMSB) Manual. 15 th Edition (UK edition). Queensland: ANZBA